150k views
4 votes
How do I work this out, I've tried


(6)/(4) = (k * - 4)/( - 4)
and that gave me

(1)/( - 1.5) x


How do I work this out, I've tried (6)/(4) = (k * - 4)/( - 4) and that gave me (1)/( - 1.5) x-example-1
User Karim AG
by
5.1k points

1 Answer

6 votes

Answer:

The required answer is
y=-\mathbf{(3)/(2)}x\\

Explanation:

We are given that value of x and y vary directly so , if two values vary directly we can write

y∝x

y=kx

Now, we are given x=-4 and y=6 and we have to fill in the blank. We actually have to find value of k i.e y=____x . Yhe blanks must be filled by value of k because y=kx

Using values of x and y i.e x=-4 and y=6 to find value of k


y=kx\\6=k(-4)\\Divide \ both \ sides \ with \ -4\\(6)/(-4)= (k(-4))/(-4) \\k=(-3)/(2)

The value of k is
\mathbf{(-3)/(2)}

So, the required answer is
y=-\mathbf{(3)/(2)}x\\

User HiveHicks
by
5.9k points